2014
DOI: 10.3892/mmr.2014.2927
|View full text |Cite
|
Sign up to set email alerts
|

Increased monocytic CD14+HLADRlow/− myeloid-derived suppressor cells in obesity

Abstract: Obesity is associated with numerous immunological disorders. The present study investigated the proportion and phenotype of myeloid‑derived suppressor cells (MDSCs) in the plasma of obese subjects and the association of these cells with the level of liver enzymes. Certain features of the immune response in obese subjects were examined by analyzing the expression of T cell receptor‑ζ (TCRζ) molecules on the surface of T cells. The expression and secretion of S100A9, a possible marker for MDSCs, were detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
3
27
0
Order By: Relevance
“…Other studies have shown an association of peripheral MDSCs with age [29] and obesity [30, 31], risk factors associated with poorer outcomes in pancreatic cancer patients [32]. We were unable to correlate the frequency of MDSC in the spleen with these clinical characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have shown an association of peripheral MDSCs with age [29] and obesity [30, 31], risk factors associated with poorer outcomes in pancreatic cancer patients [32]. We were unable to correlate the frequency of MDSC in the spleen with these clinical characteristics.…”
Section: Discussionmentioning
confidence: 78%
“…In adults, S100A8/S100A9 are strong positive regulators of MDSCs (11)(12)(13)(14)(15)(16)(17)(18)(19). Assuming that neonatal DR 2 Mos, like adult DR 2 Mos, represent Mo-MDSCs, we speculated that their expansion in newborns is due to the previously demonstrated high perinatal release of S100A8/S100A9 (6).…”
Section: Dr 2 Mos Are Expanded In Human Newbornsmentioning
confidence: 90%
“…We previously showed that newborn Mos massively release the alarmins S100A8 and S100A9 upon birth (6). Because S100A8/ S100A9 are major regulators of MDSCs in adults (11)(12)(13)19), we initially hypothesized that S100A8/ S100A9 cause an expansion of Mo-MDSCs that might contribute to an immunocompromised state in neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, there are few studies examining the impact of obesity on MDSC accumulation. However, a small cohort study from Bao and colleagues observed an increase in MDSCs in the peripheral blood of overweight/obese male Chinese subjects (BMI > 25 kg/m 2 ) compared to lean male healthy controls (BMI < 25 kg/m 2 ) …”
Section: Effects Of Obesity On Immune Subsetsmentioning
confidence: 98%